2018
DOI: 10.1186/s13104-018-3606-0
|View full text |Cite
|
Sign up to set email alerts
|

Goat pasteurellosis: serological analysis of circulating Pasteurella serotypes in Tanqua Aberegelle and Kola Tembien Districts, Northern Ethiopia

Abstract: ObjectivesA cross-sectional study was employed with the aim to explore the serological status of goats; we evaluated the presence of serum antibodies of the circulating serotypes of the genus Pasteurella. A total of 124 serum samples were collected from randomly selected goats and subsequently serotyped using indirect haemagglutination test.ResultsIn the current study, the overall prevalence of pasteurellosis in goats was 31.4%. Additionally, a total of eight serotypes of Pasteurella were serotyped. It is evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…In addition, co-infection with two or more serotypes on a single animal has been well recorded in almost all sampled (90.17%) animals. Similar findings have been reported by ( 11 , 45 ) in Northern Ethiopia. Whether multiple serotype infection exhibits a different clinical or immunological outcome as opposed to mono-serotype infections is an area of further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, co-infection with two or more serotypes on a single animal has been well recorded in almost all sampled (90.17%) animals. Similar findings have been reported by ( 11 , 45 ) in Northern Ethiopia. Whether multiple serotype infection exhibits a different clinical or immunological outcome as opposed to mono-serotype infections is an area of further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…These results are nearly similar to that obtained by Momin et al (2011) who recovered P. multocida from black Bengal goats with a rate of 20% and Rashid et al (2013) who recovered P. multocida from goat lungs with a rate of 15% respectively. However, the overall prevalence of pasteurellosis in goats was 31.4% observed by Assefa et al (2018) contrasting our result.…”
Section: Resultscontrasting
confidence: 99%
“…Few previous studies attempted to identify the serotypes of bacteria involved in eld cases of pneumonic pasteurellosis of sheep and goats. For instance, in two districts of northern Ethiopia (Tanqua-Abergelle and Kola Tembien) 9 reported the predominance of P. multocida serotype A, M. haemolytica serotype A1, M. haemolytica serotype A2, and M. haemolytica serotype A7 in goats. Similar studies conducted by Berhe et al 10 showed the occurrence of these four serotypes in sheep and goats in Tanqua-Abergelle district.…”
Section: Respiratory Diseases Of Sheep and Goats Received Huge Veteri...mentioning
confidence: 99%